Babesia microti real‐time polymerase chain reaction testing of Connecticut blood donors: potential implications for screening algorithms. Issue 11 (27th February 2013) - Johnson, Stephanie T.; Van Tassell, Eric R.; Tonnetti, Laura; Cable, Ritchard G.; Berardi, Victor P.; Leiby, David A.
<x xml:space="preserve">Abstract</x> Background Babesia microti, an intraerythrocytic parasite, has been implicated in transfusion transmission. B. microti seroprevalence in Connecticut (CT) blood donors is approximately 1%; however, it is not known what percentage of donors is parasitemic and poses a risk for transmitting infection. Therefore, we determined the prevalence of demonstrable B. microti DNA in donors from a highly endemic area of CT and compared observed rates with concurrent immunofluorescence assay (IFA) testing results. Study Design and Methods Blood samples from consenting donors in southeastern CT were collected from mid‐August through early October 2009 and tested by IFA for immunoglobulin G antibodies and real‐time polymerase chain reaction (PCR) for B. microti DNA. IFA specificity was determined using blood donor samples collected in northwestern Vermont (VT), an area nonendemic for Babesia. Results Of 1002 CT donors, 25 (2.5%) were IFA positive and three (0.3%) were real‐time PCR positive. Among the three real‐time PCR–positive donors, two were also IFA positive, while one was IFA negative and may represent a window period infection. The two IFA‐ and real‐time PCR–positive donors appeared to subsequently clear infection. The other real‐time PCR–positive donor did not provide follow‐up samples. Of 1015 VT donors tested by IFA, only one (0.1%) was positive, but may have acquired infection during travel to an endemic area. Conclusion We prospectively identified several real‐time PCR–positive blood donors, including an IFA‐negative real‐time PCR–positive donor, in an area highly endemic for B. microti. These results suggest the need to include nucleic acid testing in planned mitigation strategies for B. microti.